2019
DOI: 10.1186/s11671-019-2920-3
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the structural, electrical, and optical properties of hydrothermally grown phosphorus-doped ZnO nanorods for optoelectronic device applications

Abstract: The phosphorus-doped ZnO nanorods were prepared using hydrothermal process, whose structural modifications as a function of doping concentration were investigated using X-ray diffraction. The dopant concentration-dependent enhancement in length and diameter of the nanorods had established the phosphorus doping in ZnO nanorods. The gradual transformation in the type of conductivity as observed from the variation of carrier concentration and Hall coefficient had further confirmed the phosphorus doping. The modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…In this it is observed that the emission centered at 387 nm is associated with the electronic transition Zn i0 → VB, emission centered at 395 nm with the CB → V Zn transition, emission centered at 411 nm at Zn i0 → V Zn electronic transition, the emission of 439 nm to the electronic transition Zn i → BV. The band centered at 602 nm at the CB → O zn and CB → O i transitions and nally, the band focused on 688 nm was associated with the electronic transitions Zn i → Ozn and Zn i → O i , which is consistent with what was reported Özgür et al (2005b) and recently by Siva et al (2019) . These latter observed a yellow band (574-587) nm that they associate with the presence of Oi and a band between (678-729) nm associated with excess oxygen or oxygen vacancies (V 0 ) sites.…”
Section: Optical Propertiessupporting
confidence: 90%
“…In this it is observed that the emission centered at 387 nm is associated with the electronic transition Zn i0 → VB, emission centered at 395 nm with the CB → V Zn transition, emission centered at 411 nm at Zn i0 → V Zn electronic transition, the emission of 439 nm to the electronic transition Zn i → BV. The band centered at 602 nm at the CB → O zn and CB → O i transitions and nally, the band focused on 688 nm was associated with the electronic transitions Zn i → Ozn and Zn i → O i , which is consistent with what was reported Özgür et al (2005b) and recently by Siva et al (2019) . These latter observed a yellow band (574-587) nm that they associate with the presence of Oi and a band between (678-729) nm associated with excess oxygen or oxygen vacancies (V 0 ) sites.…”
Section: Optical Propertiessupporting
confidence: 90%
“…These parameters were chosen from the optimum values described in the literature. In order to optimize the morphology of the ZnONWs, the growth time was varied. A series of glass-ITO substrates containing ZnONWs were prepared at different times by fixing the following parameters: deposition of the seed layer by spin-coating with a thickness close to 10 nm, , temperature at 90 °C, ,, concentrations of [Zn­(NO 3 ) 2 ] = [HMTA] = 25 mM, reaction in an autoclave, and a medium volume of 15 mL. All the synthesis procedures under the chosen conditions resulted in controlled and reproducible nanowire growth.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For the optimization of the synthetic route of ZnONWs, the temperature, the precursors’ concentrations, pH, the thickness, and the producing method of the seed layer were fixed. These parameters were chosen from the optimum values described in the literature. In order to optimize the morphology of the ZnONWs, the growth time was varied. A series of glass-ITO substrates containing ZnONWs were prepared at different times by fixing the following parameters: deposition of the seed layer by spin-coating with a thickness close to 10 nm, , temperature at 90 °C, ,, concentrations of [Zn­(NO 3 ) 2 ] = [HMTA] = 25 mM, reaction in an autoclave, and a medium volume of 15 mL.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of ZnO nanostructures having different morphological shapes and attractive electronic and optical properties can be grown using inexpensive synthesis methods. 11 The optical, electronic and magnetic properties of ZnO can be tuned by doping it with suitable elements 5,12–16 and also by controlled defect creation. 17–21 Semiconductors doped with magnetic impurities are known as dilute magnetic semiconductors (DMS).…”
Section: Introductionmentioning
confidence: 99%